The fabulous Foskett family circus - Blake, Quentin; Yeoman, John (London : Andersen Press, 2015)
Roll up, roll up for the Fabulous Foskett Family Circus! There are Milly and Willy who perform with young Fred, who does a back flip and lands on his head. Uncle Phoenix Foskett who blows smoke rings, Jess and Bess with their conjuring tricks, not to mention singing dogs and birds and performing parrots. And at the end of all that excitement it is time for a well earned rest.
Primary
800-899
Keywords: Circus -- Juvenile literature